2019
DOI: 10.1128/aac.02264-18
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effect of Allopurinol in Combination with Nitroheterocyclic Compounds against Trypanosoma cruzi

Abstract: Combination therapy has gained attention as a possible strategy for overcoming the limitations of the present therapeutic arsenal for Chagas disease. The aim of this study was to evaluate the effect of allopurinol in association with nitroheterocyclic compounds on infection with the Y strain of Trypanosoma cruzi. The in vitro effect of allopurinol plus benznidazole or nifurtimox on intracellular amastigotes in infected H9c2 cells was assessed in a 72-h assay. The interactions were classified as synergic for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…Accumulating evidence has indicated that combination therapy is a promising approach to achieve a better response in the treatment of T. cruzi experimental infection (5,9,16,(22)(23)(24). In this context, a proof-of-concept evaluation of new benznidazole-sparing regimens in combination with E1224 and in monotherapy is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that combination therapy is a promising approach to achieve a better response in the treatment of T. cruzi experimental infection (5,9,16,(22)(23)(24). In this context, a proof-of-concept evaluation of new benznidazole-sparing regimens in combination with E1224 and in monotherapy is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Experimental Pharmacology 2021:13 in T. cruzi infection outcome. 172,181 Sequential treatment with allopurinol and BNZ was able to reduce parasitemia and attenuate tissue damage in infected mice. 182 Generally, drug association allows to decrease the duration of the treatment limiting adverse effects related to time-dependent drug accumulation.…”
Section: Dovepressmentioning
confidence: 99%
“… 169–171 Differently, Mazzeti et al demonstrated that this drug did not affect the evolution of Y acute infection in mice. 172 …”
Section: Drug Repurposingmentioning
confidence: 99%
See 2 more Smart Citations